An 8-year-old child with Encephalitis Rabies due to delayed case finding, proper Post Exposure Prophylaxis for Rabies infection a case report - ANDRI, ADRIANUS (Universitas Hang Tuah, 2024)
Background and Purpose: Until April 2023, it has been documented about 31.113 case of animal rabies-borne bite, which 23.211 cases are given Post Exposure Prophylaxis Anti Rabies Vaccine and 11 death cases in Indonesia and 95% of them are caused by dog bite. This case report was conducted to describe a rare case of an 8 years old child presenting with late complication of encephalitis in Borong General Hospital due to the delayed case finding, management and proper prophylaxis for Rabies infection. Case: One day prior to admission, an 8-year-old girl with irritability, aggressive behavior, and severe speech abnormalities reported to the emergency room. These symptoms quickly escalated to confusion and disturbed mental status. One month before to presentation, the patient's parents stated that his right arm had been bitten by a stray dog. Because there were no obvious bite marks and the family was not aware of the dog bite, PEP was not requested. In the previous five days, her parents described experiences of hydrophobia, photophobia, and aerophobia. The patient's health deteriorated two hours after admission, and palpating the carotid artery revealed that there was no pulse. Despite performing cardiopulmonary resuscitation, ROSC was not reached. Conclusion: Animal rabies control and surveillance are essential, particularly in locations where the disease is endemic. PEP is extremely effective and ought to be given as soon as possible following an exposure to reduce the high fatality rate. Keywords: aware, PEP, mortality, irritability